2018
DOI: 10.1080/10942912.2018.1440239
|View full text |Cite
|
Sign up to set email alerts
|

Study of golden pompano (Trachinotus ovatus) freshness forecasting method by utilising Vis/NIR spectroscopy combined with electronic nose

Abstract: Golden pompano (Trachinotus ovatus) quality forecasting method utilising Vis/ NIR spectroscopy combined with electronic nose (EN) was investigated in this article. Responses of Vis/NIR spectroscopy and EN to pompanos stored at 4°C were measured for 6 days. Physical/chemical indexes including texture, total volatile basic nitrogen, pH, total viable counts, and human sensory evaluation were synchronously examined as quality references. Chemometric methods including principal component analysis (PCA) and stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Electronic noses, which have already been tested considerably in various fields [7][8][9][10][11][12][13][14][15], provide a rapid and predictive response and represent a valid support compared to the traditional more time-consuming laboratory methods.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic noses, which have already been tested considerably in various fields [7][8][9][10][11][12][13][14][15], provide a rapid and predictive response and represent a valid support compared to the traditional more time-consuming laboratory methods.…”
Section: Introductionmentioning
confidence: 99%
“…Complex biological reactions still take place in the bodies of dead fish. The pH of fish gradually decreases with the accumulation of lactic acid caused by biophysiological activities in the rigour stage (Zhang et al, 2018). Subsequently, the fish becomes soft and enters the stage of decay and autolysis until ATP is completely decomposed.…”
Section: Phmentioning
confidence: 99%
“…Recently, many late‐model techniques, such as computer vision, spectroscopic, electronic nose, and multi‐source information fusion, have been widely used to detect meat freshness. Among them, near‐infrared spectroscopy (NIRS, 900–2,500 nm) and hyperspectral imaging (HSI, 400–1,000 nm) have been widely used to detect the freshness of chicken (Khulal, Zhao, Hu, & Chen, 2016), mutton (Jiang et al, 2018; Qiu et al, 2018 ), duck (Qiao et al, 2017), pork (Lee, Kim, Lee, & Cho, 2018; Qu et al, 2018), beef (Ma et al, 2012; Crichton et al, 2017), fish (Huang et al, 2014; Zhang et al, 2018) and other meat products due to their advantages of rapidity, non‐destructiveness and no pollution in the process of detecting meat products. In addition, multi‐source information fusion technique has attracted great attention of domestic and foreign researchers recently.…”
Section: Introductionmentioning
confidence: 99%
“…Wu, Yang, Zhou, Lai, and Zhong (2019) developed an improved non‐destructive measurement method for salmon freshness based on spectral and image information fusion, which effectively improved the accuracy of salmon freshness prediction model. Zhang et al (2018) studied golden pompano freshness based on the fusion of Vis/NIR spectroscopy and electronic nose, which presented a forecasting accuracy of 93.3%. Khulal, Zhao, Hu, and Chen (2017) evaluated the TVB‐N content in chicken based on the fusion model of colorimetric sensor and HSI, the results showed that multiple sensor fusion and the improved multiple level data fusion technique had better model performance to evaluate chicken meat freshness.…”
Section: Introductionmentioning
confidence: 99%